Multifunction trolley (Children) - Muhammad Izzat Shazali, Mohd Ramli (2009)
This report is about development of trolley that always seen used. This trolley is normal shopping trolley but added with few multifunction. It also a device which is important in order to ease transportation and to decrease the load when we want to lift or transport heavy items from one place to another. The idea of the fabricating of this trolley is based on student’s creativity. The selection of suitable materials in the fabricating of this trolley is a loaded material which has minimum weight, long life-span and can detain heavy load. For this project, the material that Materials that had been use consist of many kind of material such as hollow steel, aluminium, plate steel and others. In this report, we’ll also be having more to the fabrication of this trolley.